The role of black South African soldiers in the Second World War : a contested contribution (Historia, 2021)
Approximately 76 000 black South Africans joined the Union Defence Force (UDF) during the Second World War, thus constituting one quarter of the active South African forces supporting the Allies' war effort. In addition, there were also a large number of unattested blacks (between 15000 and 22 500) as well as an unspecified number of "casual labourers" in military bases throughout the country . The main aim of the article is to address and assess the issue of the contribution of these black men to the Allied War effort. To reach such an assessment might be easier said than done because of the difficulty of precisely defining and evaluating a "contribution".
Keywords: Union Defence Force (UDF); black South Africans; Second World War; supporting the Allies; contribution